Rural self-employment training Institutes - Raghavarao, K. (Kurukshetra: A Journals on Rural Development)
The unemployment rate in urban areas was recorded nearly 6 percent while in rural areas it was nearly 10 percent. According to the latest data, there may be 18.9 million unemployed people in India by December 2019. Due to COVID-19, this number may increase further. To tackle the issue of unemployment, self-employment is the best alternative. To fulfill this cause, the Ministry of Rural Development (MoRD) has opted the concept of Rural Self Employment Training Institutes (RSETIs). The role played by RSETIs in India is to facilitate youth to start their own business by providing them skill upgradation programmes and training them in latest technologies. The RSETIs are extending their support to the youth who are willing to take up self-employment activities. The entrepreneurship development in rural youth has to take place by stimulating their mind followed by bringing in the appropriate technology training and credit within their reach. Reproduced
Keywords: Rural unemployment, Rural youth, Self-employment, Rural entrepreneurship